Early Life Stress and Gut Microbiome Dysbiosis: A Narrative Review - Alejandro Borrego-Ruiz; Juan J. Borrego (Stresses)
Background: Exposure to early life stress significantly increases the risk of psychopathology later in life. However, the impact of early life stress on the gut microbiome and its potential role in mental health outcomes remains insufficiently understood. This narrative review examines the current knowledge on how early life stress and its associated consequences may affect the gut microbiome, with a particular focus on conditions such as anxiety, depression, and post-traumatic stress disorder. Method: A comprehensive literature search was conducted in the PubMed and Web of Science databases between January and February 2025, covering studies published between 2015 and 2025. Results: Early life stress can profoundly impact cognitive function and neurodevelopment, with maternal early-life nutrition playing a significant role in modulating the effects of prenatal and postnatal stress. Early life stress influences the gut microbiome, disrupting its composition and function by altering the synthesis of microbial metabolites, neurotransmitters, and the activation of key metabolic pathways. However, the precise role of the gut microbiome in modulating stress responses during childhood and adolescence has not yet been fully elucidated. Conclusions: Several studies have demonstrated an association between early life stress and the gut microbiome. However, causality has not yet been established due to the numerous intrinsic and extrinsic factors influencing the microbiome-gut–brain axis. In the coming years, research on key microbial regulators, such as short-chain fatty acids, amino acids, and psychobiotics, may represent a promising approach for addressing central nervous system alterations linked to early life stress. Thus, further studies will be necessary to evaluate their potential as therapeutic agents.